Role of shape on the forces on an intruder moving through a dense granular medium. (18th August 2022) - Tripura, Bitang Kwrung; Kumar, Sonu; Anki Reddy, K.; Talbot, Julian
Abstract: We use numerical simulation to investigate the effect an intruder's shape has on the drag and lift forces that it experiences while moving through a granular medium composed of polydisperse disks of mean diameter d . The intruder velocity, v, was varied from 0.1 d g to 20 d g . For frictionless particles ( μ = 0.0 ), there is a gradual increase in drag force with increasing v, whereas, for frictional systems ( μ = 0.1, 0.5 ), a constant drag regime appears at low velocities. The drag force depends weakly on the object's shape provided that its cross-section is constant. The drag force depends linearly on the immersion depth, while the lift force varies weakly with depth for certain shapes. The lift experienced by the object is a strong function of its shape at a given velocity. The shape has an effect on the distribution of contacts around the surface of the intruder, which may result in a strong lift for certain shapes. We also present and discuss the force profiles around the intruder surface.